The recency ratio as an index of cognitive performance and decline in elderly individuals. Issue 9 (20th October 2016) - Bruno, Davide; Reichert, Chelsea; Pomara, Nunzio
ABSTRACT: Individuals with Alzheimer's disease have been found to present a typical serial position curve in immediate recall tests, showing poor primacy performance and exaggerated recency recall. However, the recency advantage is usually lost after a delay. On this basis, we examined whether the recency ratio (Rr), calculated by dividing recency performance in an immediate memory task by recency performance in a delayed task, was a useful risk marker of cognitive decline. We tested whether change in Mini-Mental State Examination (MMSE) performance between baseline and follow-up was predicted by baseline Rr and found this to be the case ( N = 245). From these analyses, we conclude that participants with high Rr scores, who show disproportionate recency recall in the immediate test compared to the delayed test, present signs of being at risk for cognitive decline or dysfunction.